1999
DOI: 10.1007/s004420050961
|View full text |Cite
|
Sign up to set email alerts
|

Role of brown bears ( Ursus arctos ) in the flow of marine nitrogen into a terrestrial ecosystem

Abstract: We quantified the amount, spatial distribution, and importance of salmon (Oncorhynchus spp.)-derived nitrogen (N) by brown bears (Ursus arctos) on the Kenai Peninsula, Alaska. We tested and confirmed the hypothesis that the stable isotope signature (δN) of N in foliage of white spruce (Picea glauca) was inversely proportional to the distance from salmon-spawning streams (r=-0.99 and P<0.05 in two separate watersheds). Locations of radio-collared brown bears, relative to their distance from a stream, were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
229
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(238 citation statements)
references
References 23 publications
(20 reference statements)
6
229
1
Order By: Relevance
“…The consumption of salmon by species varied widely among bears, age class, sex, and location [92,93]. Studies have shown that bears transferred MDN to terrestrial systems through excrement and urine [94] and to riparian forests by physically moving salmon carcasses [91] via foraging activities to enhance soil nitrogen pools, and thus beneficial to many other terrestrial organisms including plants, beetles, flies, and birds [95][96][97][98][99][100][101][102][103].…”
Section: Impacts Of Aquatic Resource Subsidies On Specific Terrestriamentioning
confidence: 99%
“…The consumption of salmon by species varied widely among bears, age class, sex, and location [92,93]. Studies have shown that bears transferred MDN to terrestrial systems through excrement and urine [94] and to riparian forests by physically moving salmon carcasses [91] via foraging activities to enhance soil nitrogen pools, and thus beneficial to many other terrestrial organisms including plants, beetles, flies, and birds [95][96][97][98][99][100][101][102][103].…”
Section: Impacts Of Aquatic Resource Subsidies On Specific Terrestriamentioning
confidence: 99%
“…Bears act as "engineers" of nutrient transfer in riparian areas when they feed on salmon because they defecate (and urinate) digested fish material and drag carcasses into the forest, thereby transferring marine-derived nutrients front the aquatic to the terrestrial systems (Bilby et al 1996;Ben-David et al 1998;Willson et al 1998;Hilderbrand et al 1999b). The marine-derived nutrients and energy in salmon tissue enhances freshwater productivity (Wipfli et al 1999) and is also utilized by riparian plants and animals (Bilby et al 1996;Ben-David et al 1998).…”
Section: Salmon Attributesmentioning
confidence: 99%
“…Growth and energy storage among stream-dwelling fishes is increased by MDN (Bilby et al 1996, Wipfli et al 2003, Heintz et al 2004, Rinella et al 2012) and the direct consumption of eggs and carcass material appears to be more important than bottom-up pathways for conveying MDN benefits (Scheuerell et al 2007, Denton et al 2009, Armstong et al 2010. MDN is transferred to the riparian environment by hyporheic processes, flooding, and terrestrial scavengers (Cederholm et al 1989, Ben-David et al 1998, Hilderbrand et al 1999, O'Keefe and Edwards 2002), where it enriches riparian soils (Bartz andNaiman 2005, Drake et al 2005). Riparian vegetation can derive a substantial proportion of nitrogen from this pool (Bilby et al 2003, Reimchen et al 2003, which may lead to enhanced growth rates Naiman 2001, 2002; but see Kirchhoff 2003 and.…”
Section: Introductionmentioning
confidence: 99%